Oral mucous membrane pemphigoid and pemphigus vulgaris—a retrospective two‐center cohort study - Sultan, AS; Villa, A; Saavedra, AP; Treister, NS; Woo, S‐B (Oral diseases, 2017)
Objectives Few studies have compared oral mucous membrane pemphigoid (MMP) and pemphigus vulgaris (PV). Descriptive analysis of oral features, extent of extra‐oral involvement, and management outcomes were performed. Subjects and Methods Patients with PV and MMP, the latter with exclusive oral involvement at first presentation, were included. Results There were 26 MMP (46%) and 31 PV (54%) patients. Desquamative gingivitis was evident in 84% of MMP cases compared to 28% of PV cases (P < 0.05). Non‐gingival lesions were noted in 6% of MMP cases compared to 55% of PV cases (P < 0.01). Management of MMP consisted of only topical corticosteroids in 88% of cases while 12% of cases required concomitant systemic therapy. All PV cases (100%) required systemic therapy. No patients with MMP developed scarring or ocular lesions, and one patient (4%) developed cutaneous lesions. Five PV cases (16%) had oral cavity involvement only with three (60%) developing pharyngeal involvement and two (40%) developing cutaneous lesions on follow‐up. Conclusion Oral MMP presents primarily as desquamative gingivitis, infrequently involving extragingival sites, and is highly amenable to topical therapy, while PV is a systemic mucocutaneous disease with extensive non‐gingival oral lesions that almost always requires systemic therapy.